PESANTREN SEBAGAI BASIS PENDIDIKAN SPRITUAL DALAM PEMBENTUKAN KARAKTER JATI DIRI MANUSIA - Sakir, Moh (IAIN Ponorogo, 2015)
Abstract: In Islamic boarding schools, teachers do not only transfer religious sciences to the students, but also transform the importance of spiritual education as the first step in building human identity. Human beings have been already giveninnate essential elements by Allah as perfect complementsto be his vicegerent or khalifafilardli. To carry out this task, they must know in advance the principal elements or components that affect human spiritual characters. These componentsare the heart, intellectual and passion. These three components can be developed or trainedin sequence process of learning so that they know how to educate their heart, intellectual and passion, and eventually these lead their awareness as human beings who havepersonal identity as spiritual in nature.Â ÙØ£ Ø®ÙØ´ÙØ§ ÙØ¨ Ù Ø§Ù ØØ¨Ø³ØÙ Ø¨ÙØ§Ø·ÙØ§ ÙØ§ÙØ°Ø£ ÙÙØ¥ Ø©ÙÙÙØ¯ÙØ§ ØªØ§Ù ÙÙØ¹ÙÙ Ø§ ÙÙÙØª ÙØ§ â ÙÙØªØ±ÙØ³Ø¨ â Ø©ÙÙØ¨ØªØ±ÙØ§ Ø©Ø³Ø³Ø¤ÙÙ Ø§ ØªÙØ§ÙÂ Ø³ÙÙ ÙÙ ØªÙØ§Ù .ÙØ§Ø³ÙÙØ¥Ø§ Ø©ÙØµØ®Ø´ ÙÙÙÙØª ÙÙ ÙÙÙØ£ Ø©ÙØ·Ø®Ù Ø©ÙØÙØ±ÙØ§ Ø©ÙØ¨ØªØ±ÙØ§ Ø©ÙÙ ÙØ£ ÙÙØ°Ù Ø³Ø±Ø¯Øª Ø§ÙÙÙÙ ØÙÙØ§ÙÙÂ ÙØ°Ù Ø¡Ø§Ø¯Ø£ ÙÙÙ .ÙØ¶Ø±Ø£ ÙÙ ÙÙÙØ§ Ø©ÙÙÙØ® ÙÙÙÙ ÙÙ Ø©ÙÙ ÙÙ Ø±ØµØ§ÙØ¹Ù ÙÙÙØ§ Ø§ÙÙÙØ® ØªÙÙØ§ Ø©ÙÙÙÙØ Ø±ØµØ§ÙØ¹ ÙØ£ Ø¹Ø¶ÙÙ ÙØ§Ø³ÙÙØ¥Ø§Â ÙÙ Ø±ØµØ§ÙØ¹ÙØ§ ÙØ°Ù .ÙÙØ¯Ù Ø©ÙØÙØ± Ø©Ø¹ÙØ¨Ø· ÙÙ Ø±Ø«Ø¤Øª ÙØªÙØ§ Ø©ÙØ³Ø§Ø³ÙØ£Ø§ Ø±ØµØ§ÙØ¹ÙØ§ ÙØ§ÙØ£ ÙØ±Ø¹Ù ÙØ£ ÙØ§Ø³ÙÙØ¥Ø§ ÙÙØ¹ Ø©ÙÙØ¸ÙÙØ§Â ÙØ§Ø³ÙÙØ¥Ø§ Ù ÙØ¹Ù ØªÙØ Ø§ÙÙÙ Ø©ÙØ¨ØªØ±ÙØ§ Ø©ÙÙÙ Ø¹ ÙÙØ¨Ø·Øª ÙØ£ Ø§ÙØªÙÙ ÙØª ÙÙÙÙ Ø©Ø«ÙØ§Ø«ÙØ§ Ø±ØµØ§ÙØ¹ÙØ§ ÙØ°Ù .Ø³ÙÙÙØ§Ù ÙÙØ¹ÙØ§Ù Ø¨ÙÙÙØ§Â .Ø©ÙØÙØ± Ø©Ø±Ø·Ù ÙÙ ÙØ§Ø³ÙØ¥Ù ÙØ³ÙÙ Ø©ÙÙÙØ ÙØ§Ø³ÙÙØ¥Ø§ Ù ÙØ¹Ù ÙØ±Ø®ÙØ£Ø§ ÙÙÙ ØÙØ³ÙÙÙ ÙÙÙØ¹Ù ÙØ¨ÙÙ Ø©ÙØ¨Ø±Øª Ø©ÙÙÙÙ